A class of nonlinear oscillators with non-autonomous first integrals and algebraic limit cycles - Belattar, Meryem; Cheurfa, Rachid; Bendjeddou, Ahmed; Santana, Paulo [UNESP] (University of Szeged, 2023)
In this paper, we present a class of autonomous nonlinear oscillators with non-autonomous first integral. We prove explicitly the existence of a global sink which is, under some conditions, an algebraic limit cycle. For that class, we draw the possible phase portraits in the Poincaré disk.
Keywords: algebraic limit cycles; global sink; non-autonomous first integrals